Detection of Newcastle Disease Virus by Immunohistochemistry on the Brains of Laying Birds with Clinical Signs Torticollis and Curled Toe Paralysis - Wulan, Ocie Harum; Yunita, Niken; Wuryastuty, Hastari; Wasito, Raden (KnE Life Sciences, 2017)
Poultry is one of animal protein sources that have been consumed much in Indonesia. Various of health disorders are caused by environmental changes, woof and infectious agents have caused decline in production and economic loss. One of diseases that have a big impact on poultry husbandry is Newcastle disease (ND). Newcastle disease virus (NDV) is an important disease in Indonesia, because this has spread around Indonesia and caused a big loss for poultry industry moreover, this has high morbidity and mortality and very rapid spread of the virus. The purpose of the research is to find out and determine a fast, exact and accurate, and efficient and effective application immunohistochemistry streptavidin biotin (IHK SB) test on NDV diagnosis affirmation and for NDV fast detection as a cause of disease on commercial laying hens with clinical torticollis and curled toe paralysis symptoms. The samples used in the form of tissues from 20 commercial laying hens with an indication of clinical torticollis and curled toe paralysis symptoms. Brains would be tested using streptavidin biotin. Inspection result data obtained by immunohistochemistry streptavidin biotin (IHK SB) method is analyzed in a descriptive and qualitative way. The result of the research proves that IHK SB coloration, NDV antigen could be detected on brains. Based on the result of the research, it could be concluded that IHK SB could be applied for NDV diagnosis affirmation and it proves that commercial laying hens with clinical torticollis and curled toe paralysis symptoms. Keywords: Newcastle disease virus, immunohistochemistry streptavidin biotin, torticollis, curled toe paralysis